AB0241 Plasma Micro-RNAs Potentially Associated with The Increase Risk for Cardiovascular Disease in Rheumatoid Arthritis Patients. (15th July 2016) - Paredes, S.; Taverner, D.; Vallve, J.C.; Ferre, R.; Castro, A.; Masana, L.
Abstract : Background: Rheumatoid arthritis (RA) patients are at increased risk for cardiovascular diseases and an accelerated atherogenesis is considered the cause of this increase. MicroRNAs (miRs) are small, non-coding RNA molecules which negatively regulate gene expression. Plasmatic miRs have been identified as biomarkers in a wide range of cardiovascular diseases (CVD). Objectives: To identify plasmatic miRs in RA patients that can facilitate earlier diagnosis of CVD and provide insight regarding the increase risk for CVD in these patients. Methods: We compared plasmatic profiles of 754 miRs in 7 RA patients without CVD, in 7 patients with acute myocardial infarction (AMI) but without RA, and in 7 healthy controls with the objective to find miRs commonly expressed in the two groups of patients but at different levels from the controls. All participants were male and were matched for age and for classical cardiovascular risk factors. Plasma profile of miRs were analyzed by real time PCR using validated TaqMan® OpenArray® MicroRNA panels which enables the quantification of 754 human miRNAs. Differential expression was analyzed with Expression Suite software. Selected miRs were further analyzed with 2 -DDct method. Kruskal-Wallis test and Dunns post- test were used for the statistical analyses. Results: We were able to measure in the three groups, 50% (379) of the miRs represented in the array. Plasma profile of circulating miRs in RA and AMI patients were different from the controls. Plasma miRs that were commonly expressed in AR and AMI and expressed significantly different versus controls were: mir-Let-7a, miR-96, miR-381, miR-451, miR-518d, miR-425–5p, miR-572, miR-190b, miR-708, and miR1180. Interestingly, all 10 miRs were down-regulated compared with controls. Furthermore, 9 miRs were differentially expressed in AMI patients versus controls and 16 miRs in RA patients versus controls. Conclusions: In the present study we have identified a group of 10 miRs that potentially can be involved in the increase risk for CVD seen in RA patients. Among all these miRs, miR-451 and Let-7a have been previously associated with CVD and it might be the best candidates for future validation studies. Disclosure of Interest: None declared